Pendampingan Pemanfaatan Teknologi Artificial Intelligence (AI) Untuk Meningkatkan Kompetensi dan PTK Guru Ekonomi SMA Di Kota Mataram - Nurabiah, Nurabiah; Pusparini, Herlina; Fitriyah, Nur; Bambang, Bambang; Mariadi, Yusli; Hasanah, Huswatun; Putri, Helmiati; Fidduha, Arsyadila Sophia (Universitas Mataram, 2025)
Many teachers face difficulties in writing scientific articles due to limited time, confusion in choosing topics, a lack of ideas, low enthusiasm, and insufficient understanding of how to write them. Artificial Intelligence (AI) can be a helpful solution in overcoming these challenges. This program aims to enhance the understanding and use of AI among high school economics teachers in the city of Mataram. Several methods were used in implementing this program, including conducting a survey to identify the challenges faced, administering a pre-test to assess the teachers' initial knowledge of AI, delivering presentations on AI, providing a post-test for evaluation, and offering both offline and online consultation after the activity. This program was attended by 15 participants. The results showed that 62% of respondents demonstrated a good understanding, 23% showed fairly good results, and 15% showed less satisfactory results. These findings indicate that the program effectively improved teachers' knowledge of AI utilization.